2020
DOI: 10.1080/15548627.2020.1794356
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear role for Atg8-family proteins

Abstract: Despite the growing evidence that the macroautophagy/autophagy-related protein LC3 is localized in the nucleus, why and how it is targeted to the nucleus are poorly understood. In our recent study, we found that transcription factor seq (sequoia) interacts via its LIR motif with Atg8a, the Drosophila homolog of LC3, to negatively regulate the transcription of autophagy genes. Atg8a was found to also interact with the nuclear acetyltransferase complex subunit YL-1 and deacetylase Sirt2. Modulation of the acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…These results were in accordance with previous research, demonstrating that most ATGs are upregulated by nitrogen starvation, and that plant autophagy plays an important role in nutrient recycling under conditions of nitrogen and carbon starvation (Wang et al, 2019; Zhen et al, 2021). This was consistent with the fact that the activation of proteins in the ATG8 family enhances tolerance to abiotic stresses, including heat, nitrogen, carbon, and drought stress (Zhou et al, 2013; Jacomin et al, 2020; Bao et al, 2020). Further analysis of autophagosome accumulation activity showed that ATG8aOX considerably enhanced autophagosomes in the gpa1-4 mutant background under low nitrate conditions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results were in accordance with previous research, demonstrating that most ATGs are upregulated by nitrogen starvation, and that plant autophagy plays an important role in nutrient recycling under conditions of nitrogen and carbon starvation (Wang et al, 2019; Zhen et al, 2021). This was consistent with the fact that the activation of proteins in the ATG8 family enhances tolerance to abiotic stresses, including heat, nitrogen, carbon, and drought stress (Zhou et al, 2013; Jacomin et al, 2020; Bao et al, 2020). Further analysis of autophagosome accumulation activity showed that ATG8aOX considerably enhanced autophagosomes in the gpa1-4 mutant background under low nitrate conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Because the functions of different members of ATG8-like proteins are redundant (Bu et al, 2020; Jacomin et al, 2020), we overexpressed AtATG8a in the WT background to generate transgenic lines, such as ATG8aOX #3, #5, and #7, to identify the functions of AtATG8a under low-nitrogen conditions (Supplemental Fig. S2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was for instance found in the nuclei of all neurons in postmortem human brains 21 , and in cell cultures where a report suggested that it could shuttle in and out to regulate the expression of synapsin 98 . Interestingly in this context, recent report has also shown that ATG8 is present both in lysosomes and in the nucleus where it can regulate gene expression in association with transcription factors 71,99 . Such lysosomal-nuclear connections open the possibility of trapping molecules in the nucleus in abnormal conditions.…”
Section: Discussionmentioning
confidence: 97%
“…A hallmark of most LC3-interacting proteins is the presence of an LIR motif, which is required for their interaction with LC3 ( Onishi, et al, 2021 ). The requirement for LIR motifs to convey the ability of autophagy-related proteins to interact with LC3 is conserved across the eukaryotes ( Chu, 2019 ; Jacomin, et al, 2020 ). In this study, Cg NIX, Cg FUNDC1, Cg PHB2, Cg Cardiolipin, Cg P62, and Cg OPTN were identified with one or more LIR motifs, indicating their potential interaction with Cg LC3 in oysters.…”
Section: Discussionmentioning
confidence: 99%